2015
DOI: 10.4049/jimmunol.1402521
|View full text |Cite
|
Sign up to set email alerts
|

Batf2/Irf1 Induces Inflammatory Responses in Classically Activated Macrophages, Lipopolysaccharides, and Mycobacterial Infection

Abstract: Basic leucine zipper transcription factor Batf2 is poorly described, whereas Batf and Batf3 have been shown to play essential roles in dendritic cell, T cell, and B cell development and regulation. Batf2 was drastically induced in IFN-γ–activated classical macrophages (M1) compared with unstimulated or IL-4–activated alternative macrophages (M2). Batf2 knockdown experiments from IFN-γ–activated macrophages and subsequent expression profiling demonstrated important roles for regulation of immune responses, indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
78
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 54 publications
(57 reference statements)
4
78
0
Order By: Relevance
“…2b, all the conditions outlined have been met by the in silico model of the GRN. As reported by others, induction of Th1 responses required expression of either IRF1 alone or a combination of IRF8 and ETS transcriptional partners 2628, 33 (Fig. 2a, Table S2), while expression of Th2/Th17 was critically dependent on simultaneous expression of IRF4:ETS 2931 (Th2, Fig.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…2b, all the conditions outlined have been met by the in silico model of the GRN. As reported by others, induction of Th1 responses required expression of either IRF1 alone or a combination of IRF8 and ETS transcriptional partners 2628, 33 (Fig. 2a, Table S2), while expression of Th2/Th17 was critically dependent on simultaneous expression of IRF4:ETS 2931 (Th2, Fig.…”
Section: Resultssupporting
confidence: 66%
“…In essence, while the GRN architecture and main components are shared between different cell types, the spectrum of output genes regulated by the network varies with the specific cell type. This can be illustrated by the fact that although, for Th1-polarising dendritic cells, IRF1-controlled IL12p70 production appears established 26, 49 , we and others have demonstrated that IL12p70 is not produced by human LCs 2, 13, 50, 51 . This is despite the rapid up-regulation of IRF1 transcripts in LCs upon stimulation (Fig.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…It is therefore possible that IRF-1 contributes to type III IFN production in CVB3 infected islets via a positive feedback loop, and that the overall stronger type III IFN response in islets with the TC genotype is a result of a stronger positive feedback on type III IFN gene expression. The transcription factor BATF2 was recently shown to interact with IRF-1 and to positively influence the transcription of a subgroup of genes in IFNγ stimulated macrophages42. Our transcriptome analysis suggested that CVB3 infected islets with the TC genotype express more BATF2 mRNA than islets with the TT genotype (Fig.…”
Section: Discussionmentioning
confidence: 61%
“…Hematopoietic progenitors overexpressing Batf2 demonstrated a trend toward increased early myeloid differentiation 8 weeks after transplantation into lethally irradiated WT recipients (Figure 7C). Since Batf family members are known to act in cooperation with cofactors such as Irf1 (Roy et al, 2015), the observation that myeloid differentiation was even modestly increased without additional expression of cofactors was striking. In contrast to control cells overexpressing GFP alone, the overall engraftment of Batf2-overexpressing clones declined between 4 and 8 weeks post-transplant, showing that engraftment capacity is impaired (Figure 7D–E).…”
Section: Resultsmentioning
confidence: 99%